2007
DOI: 10.1111/j.1399-6576.2007.01310.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy in identifying patients with loss of consciousness in a police‐operated emergency call centre – first step in the chain of survival

Abstract: The accuracy was moderate with room for improvement. The positive predictive value was low, indicating over-triage of MECU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
9
0
2
Order By: Relevance
“…Cardiac arrest was found in only 4.9% of all patient contacts (53/1076, Figure 2 ) showing a massive overtriage of the BLS responders. This was expected as it has been described in two studies from our area: One found dispatch to acute coronary syndrome to have a positive predictive value of only 45% [ 16 ], the other a positive predictive value of only 39% when comparing persons classified as 'unconscious' in the dispatch message to the Glasgow Coma Scale-score upon arrival of the MECU at scene [ 19 ]. Emergency calls in Denmark are directed to the National Emergency Call Centre operated by the police (non-health care personnel) which may contribute to both over- and undertriage.…”
Section: Discussionmentioning
confidence: 62%
“…Cardiac arrest was found in only 4.9% of all patient contacts (53/1076, Figure 2 ) showing a massive overtriage of the BLS responders. This was expected as it has been described in two studies from our area: One found dispatch to acute coronary syndrome to have a positive predictive value of only 45% [ 16 ], the other a positive predictive value of only 39% when comparing persons classified as 'unconscious' in the dispatch message to the Glasgow Coma Scale-score upon arrival of the MECU at scene [ 19 ]. Emergency calls in Denmark are directed to the National Emergency Call Centre operated by the police (non-health care personnel) which may contribute to both over- and undertriage.…”
Section: Discussionmentioning
confidence: 62%
“…6 High overtriage rates have been reported in unconscious patients and cardiac emergencies. 6,7 Overtriage is not specific for dispatching centres, and it exists at all levels of emergency care. 8,9 After the end of Period II, ambulance resources had to be increased permanently because the demand remained constantly high.…”
Section: Principal Findingsmentioning
confidence: 99%
“…Ten years ago, a survey of prehospital care in the Nordic countries highlighted the former police-operated system as a weak link in Danish prehospital care [ 6 ]. A statement that was stressed by studies showing moderate to low accuracy in detection of acute coronary syndrome patients and patients with loss of consciousness [ 7 , 8 ]. The Danish EMCCs assess all incoming calls using a criteria-based dispatch protocol (the Danish Index for Emergency Care), which divides patients into five levels of emergency (A–E) based on their main symptoms [ 9 - 11 ].…”
Section: Introductionmentioning
confidence: 99%